Antifungal mode of action of macrocarpal C extracted from Eucalyptus globulus Labill (Lan An) towards the dermatophyte Trichophyton mentagrophytes. Issue 1 (December 2015) - Wong, Jack; Lau, Kit-Man; Wu, Yu-On; Cheng, Ling; Wong, Chun-Wai; Yew, David; Leung, Ping-Chung; Fung, Kwok-Pui; Hui, Mamie; Ng, Tzi-Bun; Lau, Clara
Abstract Background The fresh leaves ofEucalyptus globulus Labill. (Lan An ) have been used in Chinese medicine for many years to treat dermatomycosis. Macrocarpal C was isolated from this herb and identified as its major antifungal component by bioassay-guided purification. This study aims to investigate the antifungal activity of macrocarpal C againstTrichophyton mentagrophytes, which can cause tinea pedis. Methods Fresh leaves ofE. globulus were extracted with 95 % ethanol, and the resulting ethanolic extracts were dried before being partitioned withn -hexane. Then -hexane layer was then subjected to chromatographic purification to give macrocarpal C. The antifungal minimum inhibitory concentration (MIC) of macrocarpal C was determined using the standard M38-A2 method described by the Clinical Laboratory Standards Institute (CLSI). The mode of action of macrocarpal C was elucidated using three in vitro assays, including (1) a fungal membrane permeability test using SYTOX® Green; (2) a reactive oxygen species (ROS) production test using 5-(and-6)-carboxy-2′, 7′-dihydrodichlorofluorescein diacetate as a cell-permeable fluorogenic probe; and (3) a DNA fragmentation test based on terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) detection. Terbinafine hydrochloride and nystatin were used as positive controls. Results The suppression in the growth ofT. mentagrophytes following its treatment with macrocarpal C was associated with an increase in the permeability of the fungal membrane (P  = 0.0043 when compared to control); an increase in the production of intracellular ROS (P  = 0.0063); and the induction of apoptosis as a consequence of DNA fragmentation (P  = 0.0007). Conclusion This study demonstrated that the antifungal action of macrocarpal C was associated with increases of membrane permeability, intracellular ROS and DNA fragmentation.